Nutrient digestion, microbial protein synthesis, and blood metabolites of Jersey heifers fed chitosan and whole raw soybeans - Gandra, Jefferson Rodrigues; Takiya, Caio Seiti; Oliveira, Euclides Reuter de; Paiva, Pablo Gomes de [UNESP]; Tonissi e Buschinelli de Goes, Rafael Henrique de; Sena Gandra, Erika Rosendo de; Cariolano Araki, Hayne Mayumi (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2016)
This study was undertaken to determine the effects of chitosan and whole raw soybean on nutrient intake and total tract digestion, nitrogen utilization, microbial protein synthesis, blood metabolites, and energy balance of dairy heifers. Twelve Jersey heifers (6 +/- 0.5 months of age and 139.50 +/- 25.56 kg of live weight; mean +/- standard deviation) were randomly assigned to a replicated Latin square design with a 2 x 2 factorial arrangement. The experimental period consisted of 14 days of adaptation to diets, six days of sampling, and five days of washout. The experimental diets were: control (CO); chitosan (CHI, inclusion of 2.0 g kg(-1) DM of chitosan); whole raw soybean (WS, 163.0 g kg(-1) of WS on diet DM basis); and chitosan + whole raw soybean (CHI+WS). Chitosan decreased dry matter and neutral detergent fiber intakes; however, CHI increased DM total tract digestion. An interaction effect was observed on retained nitrogen, which increased when animals were fed CHI+WS compared with CO or CHI, but did not differ from that of animals fed WS. Chitosan decreased microbial nitrogen and crude protein flow of heifers. Energy balance was improved when heifers received diets containing WS. Efficiency of energy utilization was not affected by experimental diets. An interaction effect was observed for blood high-density lipoprotein (HDL) concentration, which increased with both dietary inclusion of CHI and WS compared with the other diets, and CHI provided the lowest value of HDL cholesterol. Chitosan and whole raw soybean do not alter nutrient intake and total tract digestion; however, they decrease nitrogen urinary excretion and increase blood HDL cholesterol of heifers.
Keywords: antimicrobial; nitrogen metabolism; oilseed; rumen modulator